A TRACE ELEMENT AND CHEMICAL TH-U TOTAL PB DATING STUDY IN THE LOWER BELT-PURCELL SUPERGROUP, WESTERN NORTH AMERICA: PROVENANCE AND DIAGENETIC IMPLICATIONS - González-Álvarez I.; Kerrich R.; Kusiak M.A. (My University, 2006)
Comprehensive geochemical and monazite chemical age data on the Mesoproterozoic Belt-Purcell Supergroup reveals information on provenance age(s), and the sources of interbedded argillites and sandstones. Compliance of rare earth element (REE) and multi-element patterns of argillites to post-Archean upper continental crust (PA-UCC), and Cr-Ni, and Th/Sc-Sc systematics are consistent with a dominantly post-Archean source area. Sandstones have the same geochemical fingerprint as argillite for the Appekunny and Grinnell formations in the lower Belt-Purcell Supergroup sequence, albeit variably depleted by detrital quartz. Sandstone developed in a separate high-energy environment, and argillite and sandstone became interbedded during storms, accounting for the sharp interbedding of the two facies. Detrital monazite chemical Th-U total Pb ages from the Appekunny and Grinnell sandstones, and argillites of the former, cluster at ~ 1700 Ma. Paleocurrents and chemical ages support a Laurentian Paleoproterozoic provenance, likely the Yavapai, Mazatzal and Central Plains provinces. Other potential sources could have been terranes at ~ 1875-1750 Ma that cooled through the blocking temperature of monazite ~ 1700 Ma such as the Wyoming Province. Rare > 2500 Ma monazite ages in argillite and sandstone stem for minor contributions from Archean terrane(s). Diagenetic overprint in the Belt-Purcell rocks is widespread and displayed geochemically as heavy REE enrichment relative to light REE, normalized to PA-UCC. There are two populations of monazites: the first has detrital textures, with chemical ages > ~ 1400 Ma, higher ThO2 and Y, and lower LREE/HREE content than < ~ 1400 Ma monazites with euhedral texture, ages up to ~ 900 Ma post-deposition, with lower ThO2 and Y, and higher LREE/HREE content. The second population is interpreted as the product of protracted migration of basinal brines that mobilized HREE, as documented in several Proterozoic sedimentary basins. © 2005 Elsevier B.V. All rights reserved.
Keywords: BELT-PURCELL SUPERGROUP; CHEMICAL AGE; DIAGENESIS; MESOPROTEROZOIC; MONAZITE; PROVENANCE; SEDIMENTARY ROCKS; Докембрий::Протерозой::Мезопротерозойская; Precambrian::Proterozoic::Mesoproterozoic